1870 Tex. Gen. Laws 139, ch. 73 - (:unkn) unknown (General Publisher, 1870)
Prohibited carrying “any gun, pistol, bowie-knife or other dangerous weapon, concealed or unconcealed,” within a half mile of a polling place while the polls are open.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES